EVALUATION IMPLEMENTATION OF CURRICULUM UNIT LEVEL OF EDUCATION FOR ARABIC LENGUAGE LEARNING IN MTS DDI SEPPANGE - St Jumaeda (IAIN Ambon, 2018)
Abstract: The purpose of this study is to obtain objective information and the find improvement quality process and quality output on Arabic Lenguage program. This study is an evaluative research approach using a model developed by Widoyoko, which includes two main components, namely: the quality of the process and instructional output. In this study applied studies the evaluation program, method the collection of data obtained through the study of documents, interviews, questionnaires and observation. The evaluation of the assessments made at each stage of evaluation, and decision making. The finding in that Arabic Lenguage learning program evaluation in MTs DDI Seppange, shows that the quality of the process of learning programs, including the categories of good, and the output quality of learning of Arabic Lenguage are also included in the good category. Considering these facts before, there are still some aspects in the evaluation process quality and output quality of learning that needs to be improved so that the learning of Arabic Lenguage will be more effective and achieve competence that has been planned. Key words: evaluation, learning of Arabic Lenguage